Obtenção do diagrama de radiação de antenas utilizando o método FDTD bidimensional - MORAES, Hugo Riviere Silva (2018)
This paper consists of to study the numerical analysis method called the Finite Difference Time Domain method (Finite Difference-Time-Domain Method, in English) to troubleshoot applied electromagnetism. The study aims to understand the FDTD method to apply it in calculating the distribution of electromagnetic field in rectangular coordinates in order to analyze the antenna radiation characteristics. The method was applied using the UPML boundary condition, Perfectly Matched Layer Anisotropic Uniaxial, which was used to simulate the irradiation fields in a space environment. The antennas used for study and analysis were sectoral horn plane-E and plane-H. Therefore, algorithms have been developed in FORTRAN language to calculate the values of the electromagnetic field simulation and back thereof to observe the results graphically. Such algorithms have been optimized for the user to manipulate the length and antenna aperture angle, making it possible to observe the change in behavior of the radiation characteristics. Stability criteria were analyzed algorithms for the attending results to what was proposed. The tools used were the program development environment MICROSOFT DEVELOPER STUDIO and commercial software MATLAB. The results allowed a view of the irradiation of electromagnetic fields, with greater sense of operating a complex electromagnetic structure, and also to obtain radiation diagrams of the antennas analyzed through the application of Huygens' principle.